Design of smart power grid renewable energy systems - Keyhani, Ali, 1942- (Wiley, 2019)
The Updated Third Edition Provides a Systems Approach to Sustainable Green Energy Production and Contains Analytical Tools for the Design of Renewable Microgrids. The revised third edition of Design of Smart Power Grid Renewable Energy Systems integrates three areas of electrical engineering: power systems, power electronics, and electric energy conversion systems. The book also addresses the fundamental design of wind and photovoltaic (PV) energy microgrids as part of smart-bulk power-grid systems. In order to demystify the complexity of the integrated approach, the author first presents the basic concepts, and then explores a simulation test bed in MATLAB® in order to use these concepts to solve a basic problem in the development of smart grid energy system. Each chapter offers a problem of integration and describes why it is important. Then the mathematical model of the problem is formulated, and the solution steps are outlined. This step is followed by developing a MATLAB® simulation test bed. This important book: Reviews the basic principles underlying power systems Explores topics including: AC/DC rectifiers, DC/AC inverters, DC/DC converters, and pulse width modulation (PWM) methods Describes the fundamental concepts in the design and operation of smart grid power grids Supplementary material includes a solutions manual and PowerPoint presentations for instructors. Written for undergraduate and graduate students in electric power systems engineering, researchers, and industry professionals, the revised third edition of Design of Smart Power Grid Renewable Energy Systems is a guide to the fundamental concepts of power grid integration on microgrids of green energy sources.